Wadi al jizzi archaeological project 2023 - Düring, Bleda S. (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
This paper presents the main results of the 2023 excavations at Site 73 / 66 in the Liwa hinterlands (northern Oman) undertaken by the WAJAP team. Excavations focused on domestic buildings dating to the Umm an-Nar and Wadi Suq period. Here, the buildings and the deposits found within them will be discussed.
Keywords: Archéologie – Oman